Justice on the Streets - Udvarhelyi, Éva (Socio.hu Társadalomtudományi Szemle, 2013)
With knowledge and power so intimately tied together, research and documentation can easily turn into technologies of control and exclusion. While the modern state is extremely adept at counting, documenting and categorizing its residents, it is also able to enforce certain expectations towards its citizens through a request for proper documentation. In today’s Hungary, the state has acquired a vast knowledge about people who are homeless through various forms of registration. At the same time, being properly documented is essential for homeless people in order to access necessary services and maintain their links to the body politic. By contrast, homeless people are rarely in a position either to get to know the state’s operations in detail or set expectations towards the state and its representatives. Justice on the Streets, a participatory action research (PAR) project undertaken by the homeless and housed members of The City is for All (AVM), a homeless rights advocacy group in Budapest, represents an attempt at bridging this huge inequality in knowledge and power by documenting the behaviour of the state from the perspective of street homeless people. In this paper, I use the concept of deep participation to examine the collective process of critical reflection and knowledge production in PAR. More specifically, I analyse the unfolding of deep participation in Justice on the Streets from the perspective of: 1) the development of a critical consciousness; 2) the dynamics of participation in a cross–class context; and 3) the deconstruction of power and inequality at both the micro and macro levels. KEYWORDS Homelessness, discrimination, Participatory action research, Budapest, The City is for All